Electric Power Industry: Relationship Between Total Quality Management (TQM) and Organizational Performance of Conformity Assessment Body in The Industry - Riangga Aji Prasetyo (Jurnal Indonesia Sosial Teknologi, 2025)
The Indonesian government has increased fuel prices through Decree 218.K/MG.01/MEM.M/2022. This is in response to an increase in the energy subsidy budget of IDR 502.4 trillion. Additionally, current geopolitical conditions have greatly influenced the price of energy commodities in the world market. This has caused the government to change fossil fuel usage to electrical energy. This study aims to analyze the relationship between the implementation of TQM and organizational performance in PT XYZ, as well as identify the elements of TQM that have the most significant impact on improving organizational performance. By understanding this relationship, this research is expected to provide recommendations for PT XYZ to enhance its competitiveness and operational effectiveness. The research method used is a survey by distributing questionnaires to PT XYZ employees. The data obtained was analyzed using the Structural Equation Model (SEM) method to test the correlation between variables. The study results show that implementing TQM positively and significantly affects organizational performance. Factors such as top management commitment, quality awareness, communication, and employee engagement have a dominant role in improving job satisfaction and the company's business results. The conclusion of this study confirms that TQM can be an effective strategy for increasing organizational competitiveness by improving customer satisfaction and service quality. The implications of this study highlight the importance of strengthening relationships with external providers to increase competitive advantage. In addition, the management of PT XYZ is advised to maintain a quality culture and management system that has been proven to positively impact the company's performance.